Antibacterial Potential of 2, 4-Di-tert-Butylphenol and Calixarene-Based Prodrugs from Thermophilic Bacillus licheniformis Isolated in Algerian Hot Spring. Issue 1 (2nd January 2019) - Aissaoui, Nadia; Mahjoubi, Mouna; Nas, Fatima; Mghirbi, Olfa; Arab, Mounia; Souissi, Yasmine; Hoceini, Amina; Masmoudi, Ahmed S; Mosbah, Amor; Cherif, Ameur; Klouche-Khelil, Nihel
Abstract: The present investigation reports the isolation, molecular identification and structure elucidation of antibacterial produced by two thermophilic spore-forming bacteria from hot spring (98 °C) of Guelma (Algeria). Morphological, biochemical and physiological characteristics were carried out. The molecular identification by 16S rRNA and 16-23S rRNA ITS-PCR sequencing identified the thermophilic strains as Bacillus licheniformis with 99% of similarity with GenBank accession numbers KX100031 and KX100032. Phenotypic characterization has mentioned several differences between thermophilic isolates and Bacillus licheniformis ATCC 14580. The ability of the thermophilic spore- forming bacteria to produce antibacterial compounds against two multidrug resistance bacteria Pseudomonas aeruginosa (NR_0754828.1) and Staphylococcus aureus (NR_075000.1) in pure and mixed culture was investigated by Radial Diffusion Assay at 55 °C. Structural elucidation of actives compounds was carried out using gas chromatography–mass spectrometry analyses. Antibacterial potency of the thermophilic isolates might be due to the association between two phenolic compounds: 2, 4-Di-tert-butyl-phenol as principal active compound and p-tert-butylcalix[4]arene as prodrugs comparing between gas chromatography–mass spectrometry analysis of pure and mixed extract. To the best of our knowledge, this is the first report showing production of p-tert-butylcalix[4]arene and 2, 4-Di-tert-butyl-phenol as extremolytes compounds from thermophilic Bacillus licheniformis at 55 °C.